Estabelecimento do contraste entre as fricativas por crianças com transtorno fonológico: manipulação de pistas acústicas - Corrêa, Alessandra Pagliuso dos Santos [UNESP]; Berti, Larissa [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2015)
The present study focuses on the presence of covert contrasts in the speech of children with a phonological disorder. The hypothesis is that children with phonological disorders manipulate secondary acoustic cues in an attempt to distinguish the phonological contrasts. We used five audio recordings of the speech of five children with speech disorders, between four and five years of age, who showed the so-called “phonic substitution” involving the sound group of the fricatives. The data were edited and analyzed using the software PRAAT. A phonetic transcription of the first repetition of each child was performed by three evaluators, reaching a 66% agreement level. After the transcription, we carried out a contrastive phonological analysis of the production of the five children and, finally, an acoustic analysis of all the “substitutions”, based on six parameters. We discovered the existence of covert contrasts in the productions auditorily regarded as homophones by the evaluators, representing a total of 54% of total substitutions identified through an impressionistic approach by the evaluators. Children with phonological disorders are seen to rely on secondary acoustic cues in an attempt to distinguish fricative phonemes. The data obtained in this study allow us to reflect on the importance of considering the phonetic detail within the phonological models.

O presente trabalho versa sobre a presença de contrastes encobertos na fala de crianças com transtorno fonológico. A hipótese perseguida é a de que as crianças com transtorno fonológico se ancoram em pistas acústicas secundárias na tentativa de estabelecer contrastes fônicos da língua. Para tanto, foram utilizadas cinco gravações em áudio, advindas de cinco crianças entre 4 e 5 anos com transtorno fonológico, que apresentavam as chamadas “substituições fônicas” envolvendo a classe de sons das fricativas. Os dados foram editados e analisados com o uso do software PRAAT. Foi realizada uma transcrição fonética da primeira repetição (R1) de cada criança, por três juízes, e considerada a concordância de 66%. A partir dessa transcrição, foi realizada a análise fonológica contrastiva acústica de todas as “substituições” envolvendo a classe de sons das fricativas, a partir de seis parâmetros. Verificou-se a existência de contrastes encobertos nas produções tidas como homófonas auditivamente, representando um total de 54% do total das “substituições” identificadas pelos juízes. As crianças com transtorno fonológico ancoram-se preferencialmente em pistas acústicas secundárias na tentativa de distinguir os fones fricativos. Os dados obtidos neste estudo permitem reflexão acerca da importância de se considerar o detalhe fonético no interior dos modelos fonológicos.
The establishment of phonological contrast between fricatives by children with phonological disorder: manipulation of acoustic cues
Keywords: Phonological acquisition; Phonetic; Phonological disorder; Acoustic analysis; Fricatives; Aquisição fonológica; Fonética; Análise acústica; Fricativas; Transtorno fonológico